Differential Effects of Chronic Pulsatile versus Chronic Constant Maternal Hyperglycemia on Fetal Pancreatic β-Cells - Mackenzie S. Frost; Aqib H. Zehri; Sean W. Limesand; William W. Hay; Paul J. Rozance (Journal of Pregnancy)
Constant maternal hyperglycemia limits, while pulsatile maternal hyperglycemia may enhance, fetal glucose-stimulated insulin secretion (GSIS) in sheep. However, the impact of such different patterns of hyperglycemia on the development of the fetal β-cell is unknown. We measured the impact of one week of chronic constant hyperglycemia (CHG, n=6) versus pulsatile hyperglycemia (PHG, n=5) versus controls (n=7) on the percentage of the fetal pancreas staining for insulin (β-cell area), mitotic and apoptotic indices and size of fetal β-cells, and fetal insulin secretion in sheep. Baseline insulin concentrations were higher in CHG fetuses (P<0.05) compared to controls and PHG. GSIS was lower in the CHG group (P<0.005) compared to controls and PHG. PHG β-cell area was increased 50% (P<0.05) compared to controls and CHG. CHG β-cell apoptosis was increased over 400% (P<0.05) compared to controls and PHG. These results indicate that late gestation constant maternal hyperglycemia leads to significant β-cell toxicity (increased apoptosis and decreased GSIS). Furthermore, pulsatile maternal hyperglycemia increases pancreatic β-cell area but did not increase GSIS, indicating decreased β-cell responsiveness. These findings demonstrate differential effects that the pattern of maternal hyperglycemia has on fetal pancreatic β-cell development, which might contribute to later life limitation in insulin secretion.